Journalistic Commentary in Tishreen and Al- Watan Newspapers An Analytical Study of the Journalistic Commentaries in the First Half of 2018 - alomr, Mohamad; Sbeira , Falak Hasan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed at investigating the art of journalistic commentary in Tishreen Newspaper, governmental newspaper and Al-Watan Newspaper private newspaper in Syria by analyzing the contents of journalistic commentaries that published during the first half of 2018, amounting to (680) journalistic commentaries. The study results showed a preference for the writers of Tishreen and Al-Watan Newspapers to comment on the political and sports events, local then international and Arab events, and their orientation to explain the hot events at the first place, and they employed a tool (inference to past events), With a positive trend of Tishreen’s writers against a negative trend of Al –Watan’s writers. The study recommended that the writers of two newspapers should be more closely aligned with important daily events, need to diversify journalistic issues and take into account other functions of journalistic commentary such as guidance. The study called for future research, such as analyzing the content of journalistic commentaries in the Syrian press, determining the location of the journalistic commentary, researching in methods of editing the journalistic commentary, and employing media theories in study of journalistic commentary.